Perancangan Pembahagian Harta Semasa Hidup dalam Islam: Konsep dan Kepentingannya: Planning on Wealth Distribution During Lifetime in Islam: Concept and Its Importance - Muhamad Husni Hasbulah,; Mohd Zaidi Daud, (Global Journal Al-Thaqafah, 2024)
The planning of wealth distribution during one’s lifetime is an aspect that should be practised and recognized widely. By having a wealth distribution planning, one is able to protect the interests of the owners themselves and the prospective recipients of the property, whether before or after death. Understanding the policies of the distribution of wealth based on the al-Quran and Hadith will help to guide Muslims in understanding the needs and importance of planning assets while they are still alive. Therefore, this article will explore the concept of estate planning, its value and importance in the Islamic point of view. Through this descriptive analysis, a positive change of mindset is able to be implemented onto the Muslim community on wealth distribution which would aid them in realizing that the plan is very important and should be practiced more commonly. Furthermore, various issues, that occur in relation to the distribution of property amongst Muslims, call for the need to promote comprehensive and systematic solutions. At the end of this paper, the writers will show that through wealth distribution planning completed during lifetime without having to wait for death, the problems that occur amongst Muslims with regards to the distribution of property will be mitigated.